Elimination of a Cationic Dye (Crystal Violet) in Aqueous Medium by TiO2/UV Oxidation Process - Sihem, Aliouche; Kamel, Djebbar; Halima, Chenini; Tahar, Sehili; Abdlkader, Bouchoul; Djamil Azzedine, Rouag (Asian Journal of Chemistry, 2010)
The crystal violet, a cationic dye, could be discoloured by TiO2/ UV process. The experiments have shown on one hand that direct transformation at 365 nm has led to a feeble percentage of decolourization (≈ 25 % decoloured for a reaction time of 5 h and for a concentration of 3 ppm) and in another hand adsorption process has conducted, in absence of light, to a negligible amount of dye retention. By contrast, the treatment of the considered solution by TiO2/UV at 365 nm has permitted to obtain a better efficiency of the bleaching process. It has been observed that the decolouration rate has varied with concentration of the substrate. Indeed, as the solution becomes more coloured, the colouration disappeared slowly. Moreover, in all cases, the discolouration process followed a first-order rate law. The influence of H2O2 has led to an improvement of this process marked thereby, by an acceleration of the bleaching rate. This fact could be attributed to the participation of the radicals OH•, in these reactions. In this case too, the kinetics behaviour was well represented by first-order rate law. The effects of salts such as NaCl and Na2SO4 have been also investigated and the obtained results showed a decrease of the decolouration rate for both cases. The photocatalytic pathway has been well described by the Langmuir-Hinshelwood kinetics model. The values of the rate constant (k) and adsorption equilibrium constant (K) are 1.76 M min-1 and 7.07 M-1, respectively.